The effect of supply chain integration, management commitment and supply chain challenges on non-profit organizations performance: Empirical evidence from Afghanistan - Sayed Momin Hashemi; Eko Handayanto; Ilyas Masudin; Fien Zulfikarijah; Muhammad Jihadi (Cogent Business & Management, 2022)
This research aimed to determine the effect of supply chain challenges and supply chain performance in nonprofit organization performance and the supply chain integration and management commitment in supply chain performance. One hundred questionnaires were distributed to top-level, middle-level, and lower-level managers of Afghanistan non-profit organizations. Out of 100 questionnaires distributed, 55 questionnaires were filled and returned a 55% response rate. This study adopted a quantitative method using the SmartPLS application. This study found that integrating supply chain indicators such as sharing information, planning, controlling and coordinating materials, and commitment of all three management levels positively affects supply chain performance. Moreover, this study found that challenges such as government regulation, customer pressure, and supply chains performance indicators such as supply chain delivery flexibility, customer responsiveness time, and inventory cost significantly affect non-profit organization performance.
Keywords: 650; Integration supply chain; management commitment; non-profit organization performance; supply chain challenges; supply chain performance